Effect Balance of Bokashi and Inorganic Fertilizer on Growth, Simplicia Yield, and Content Of Sinensetin of Kumis Kucing (Orthosiphon aristatus (Blume) Miq.) - Yoviana Erdhika Adiarti; Bambang Pujiasmanto; Widyatmani Sih Dewi (Universitas Sebelas Maret, 2019)
Growth potential, simplicia yields, and secondary metabolites of sinensetin varieties kumis kucing can be increased through fertilization management. The aim of this research was to examine the effect balance of bokashi and inorganic fertilizer on growth, simplicia yields and secondary metabolites of sinensetin kumis kucing varieties. The design of research was a split-plot field experiment, with the main plot were varieties (Orsina 1 and Orsina 2) and subplots in bokashi fertilization of goat manure (control, bokashi 15 tons ha-1, bokashi 15 tons ha-1 + 100% inorganic fertilizer dose recommendation, bokashi 15 tons ha-1 + 50% recommended dosage of inorganic fertilizer and 100% recommended inorganic fertilizer). Inorganic fertilizer recommendations consist of Urea 100 kg ha-1, SP36 200 kg ha-1, and KCl 100 kg ha-1. The results showed that the use of bokashi 15 tons ha-1 + 50% inorganic fertilizer increased growth. Besides it also produced the highest simplicia of 48.57 g plant-1 and the highest secondary metabolite of 0.045% plant-1 in Orsina 1. Both kumis kucing varieties did not show growth differences and yields. Bokashi fertilizer can reduce the use of inorganic fertilizers in the growth and simplicia yields and potentially increase sinensetin of kumis kucing.